Eating disorder recovery handbook : a practical guide for long-term recovery - Davies, Nicola; Bacon, Emma, 1978- (Online access with DDA: Askews (Medicine), 2017)
Thoughtfully developed activities will help you to understand, overcome, and maintain recovery from your eating disorder. This complete resource is designed for individual recovery as well as for use in counselling, schools, or self-help groups.